PENENTUAN JUMLAH PRODUKSI OPTIMAL CPO DAN KERNEL MENGGUNAKAN GOAL PROGRAMMING PADA INDUSTRI PENGOLAHAN KELAPA SAWIT - Fikri Arsil; Orlando Frandas; Fatmir Edwar (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2022)
The high demand for crude palm oil (CPO) and kernel at CPO Industry requires good production planning so that the production process runs smoothly. The utilization of the resources used is still not optimal, for this reason an effort is made to optimize the production  that they can the targets and limits set by the company. In optimizing the production of CPO and kernel, several factors must be considered, starting from production raw materials namely fresh fruit bunches, factory capacity, storage and the yield of CPO and kernel that have been set by the company. The method used in this final assignment is the Goal Programming method. This method is able to solve the problem of more than one target to be achieved (multi-objective). This’s in accordance with the conditions of the problems at CPO Industry, namely maximizing the production of CPO and kernel when processing FFB at the factory. The output of this final project is the optimal amount of CPO and kernel production for the period January 2021 to December 2021. The results of this planning optimization are expected to assist in a more effective and efficient that process to achieve the targets set by the company.